Synthesis and characterization of dithienobenzothiadiazole-based donor-acceptor conjugated polymers for organic solar cell applications - Efrem, Amsalu (2014)
New donor–acceptor conjugated polymers (P1 and P2) containing a fused-ring dithienobenzothiadiazole (DT-BTD building block) were synthesized by using the Stille copolymerization method. The synthesized polymers were characterized by 1H NMR, GPC, and elemental analysis. The optical band gaps of the polymers were found to be 1.86 and 1.9 eV, respectively, as calculated from their film onset absorption edge. Upon annealing both produced a distinct shoulder peak in their film absorption spectra. The electrochemical studies of P1 and P2 revealed that the HOMO and LUMO energy levels of the polymer were −5.3, −5.1 eV, and −3.4, −3.2 eV, respectively. The polymers are thermally stable up to 250–350 °C.